KESANTUNAN BERBAHASA DOSEN TERHADAP MAHASISWA DALAM PEMBELAJARAN BAHASA INDONESIA - Ajat Sudrajat; Masykur H. Mansyur; Slamet Sholeh (Literasi: Jurnal Ilmiah Pendidikan Bahasa, Sastra Indonesia dan Daerah, 2022)
This study describes the politeness of language carried out by lecturers to students in learning Bahasa at a private university in the Karawang district. The method in this research is the descriptive qualitative. The data in this study are in the form of lecturers' speeches containing language politeness to students in learning Indonesian. The results and discussion in this study referred to Leech's theory, the researcher found that the maxim of wisdom is 13 utterances, the maxim of generosity is 11 utterances, the maxim of praise is 15 utterances, the maxim of humility is 11 utterances, the maxim of agreement is 10 utterances, and the maxim of sympathy is 13 utterances. The total number of politeness utterances from the lecturer is 73 utterances. Furthermore, based on the interview result, the researcher found out that the lecturer remained polite, especially using language towards the speech partner. The researchers conclude that the lecturer has realized polite speech using Leech's theory, and the lecturer will continue to speak consistently to his partner, especially in the academic setting.